Interspecies association mapping links reduced CG to TG substitution rates to the loss of gene-body methylation - Kiefer, Christiane; Koch, Marcus (Nature plants, 2019)
Using genome assemblies of 47 Brassicaceae species and a new interspecies association mapping strategy, a study reveals the association between CG to TG substitution rates and the presence of CHROMOMETHYLASE3 orthologues or gene-body methylation.
Gesehen am 21.10.2019